THE SINGLE TAX PRINCIPLE AS A LIMIT TO DOUBLE NON-TAXATION? A BROAD PERSPECTIVE - Zubimendi,Alejandro (2019)
Abstract In recent years, double non-taxation phenomenon has gained some importance. This phenomenon means that income is not subject to tax anywhere. Based on a purported international tax regime, some academics have defended the existence of a single tax principle which prohibits double taxation as well as double non-taxation. From a political standpoint, States enjoy fiscal sovereignty in order to design the rules to accomplish their own fiscal policies. In the current economic context of globalization, countries compete with each other in order to attract foreign investment and capital. To achieve these goals, countries use fiscal instruments, such as public expenditure or taxes. Nevertheless, countries are different from each other and may have different goals in consideration of their preferences. There are countries that base their competitiveness on offering good public infrastructures, whereas other countries are focused on low taxation to attract foreign investment, and even there are other countries, due to their economic structure, able to secure good public infrastructures with low taxes. Therefore, a country is free and sovereign to “untax” the income over which it has tax powers. The question is whether there are limits to the tax sovereignty of countries so that they may prohibit certain forms of double non-taxation. These supranational limits might be identified in the structure of the international tax regime. These attributes of the international tax regime inform largely the tax legislation of the international community. Those principles are the interpersonal equity or ability-to-pay principle, the neutrality principle, and the justice in the allocation of the taxing powers or internation equity principle. Nevertheless, from a positivistic and public international law standpoint, these supranational principles do not bind countries to hold a minimum threshold of taxation.